Modelagem e avaliação da eficiência de caldeira flamotubular na transição do gás natural para o biometano - Nakasone, Lenrry Ryuji Shimabukuro (2025)
The growing need to reduce greenhouse gas emissions has driven the energy transition across various industries. In this context, replacing natural gas with biomethane emerges as a viable alternative, especially in processes that require steam generation. This study aimed to develop a methodology for evaluating the thermal efficiency of an industrial fire-tube boiler, with the goal of creating a reference baseline for future comparative analyses during the transition to biomethane. Initially, real operational data from the industrial plant were collected over eight months of operation using natural gas. The methodology included a rigorous data treatment process, involving the filtering of incomplete records and the elimination of inconsistent points. Subsequently, different mathematical models were tested to represent the boiler's efficiency curve, including hyperbolic, polynomial, exponential, literature-based, and hybrid models. After statistical analysis and visual evaluation, the hybrid model was selected as the most representative, considering both the determination coefficient and the physical consistency of the boiler's behavior across different operating loads. Based on the results obtained, the official efficiency curve of the boiler was defined, which will serve as a benchmark for future operational data when the transition to biomethane occurs. The developed system enables the rapid detection of performance deviations, allowing for the evaluation of the impacts caused by the fuel change. This study provides a practical contribution to energy efficiency management in the industrial sector.